A Matter of Experience? Understanding the Decline in Group Lending. (26th March 2019) - Ahlin, Christian; Suandi, Matthew
Abstract: Group lending, often considered a key innovation driving the successful expansion of microcredit across the world, appears to be on the decline. Using MIX data on microfinance institutions (MFIs), we study this time trend, focusing on macroeconomic predictors of group lending and MFI experience. Results suggest that any movement away from group lending is better explained via MFIs gaining experience rather than a secular time trend. We also find that group lending is used more extensively in poorer and low‐growth economies. We argue that these findings can be understood within established views of group lending, and carry important implications for the historical and continuing importance of group lending.